Compliance with the five moments for hand hygiene of healthcare workers in a pediatric hospital. A prospective observational study - Grau, Lorena; Perruchino, Giselle; Mesquita-Ramírez, Mirta (Medicina Clínica y Social, 2024)
Introduction:  Healthcare-associated infections (HAIs), also known as nosocomial infections or hospital-acquired infections, begin within 48 hours of hospitalization, within 30 days after hospital discharge, or 90 days after undergoing surgical procedures. Objective: The study aimed to describe the compliance with the five moments for hand hygiene (HH) of the healthcare workers (HCWs) in a hospital. Methods:  A prospective observational study was conducted from June 1 to 30,2020 in a pediatric hospital. HCWs compliance with the five moments of HH was registered by direct observation blindly to the participants, using the fact sheet for HH of the WHO. In the rows, the five moments of contact with the patients were recorded: before touching a patient, before clean aseptic procedure, after body fluid exposure risk, after touching a patient and after touching patient surroundings. The actions performed, also was registered: hand washing, alcohol hand friction, omission, or use of gloves. Data were analyzed in SPSS V 21. The protocol was approved by the institutional review board. Results: During the study period, 2.595 observations to 104 HCWs were made. They were pediatric residents 38.5 %, nurses 32.7 % and pediatricians 28.8 %. A global compliance with the five moments of HH of the participants were 64.5% (1673/2595). Before touching a patient, the adherence was 86,9%. The nurses adhered in 69%, pediatrician in 68.6 % and the pediatric residents in 57.2%. Discussion: The global percentage of compliance with the five moments of HH of the medical and nursing staff of the pediatric hospital was 64.5%. Nurses had the highest percentage of adherence. Handwashing compliance was higher before contact with the patients.